BUCIUM ŞI MOGOŞ – ÎN PREZENT ZONĂ DEFAVORIZATĂ, ÎN VIITOR POTENŢIALĂ DESTINAŢIE TURISTICĂ (PANGEEA, 2025)
Bucium – Mogos, a disadvantaged region at present, a possible future tourist destination. Due to The Government of Romania Decision (Hotararea Guvernului Romaniei nr. 813/7 octombrie 1999) the Apuseni mining region was also declared a disadvantaged region- it includes the localities Bucium and Mogos, in the Alba district. Following the negotiations Romania had with U.E, Romania promised that she would give up helping these regions, as they have done lately. The question that arises is what we can do to revive this geographic region from an economic point of view. A solution could be using the natural and human potential of the region with a touristic purpose. The area in discussion is situated in the Central - North-Western part of the Alba County, in the Poieni(Bucium) and Birlesti(Mogos) depressions. Access in zona is favored by the presence in aproxime of three European road corridors E68, E81, E79, arteries which can constitute access routes for potential foreign tourists.